Current situation of pomegranate growing (Punica granatum L.) in southern Alicante. Chemical control of pests and diseases and financial cost - Juan P.; Martínez J.; Martínez J.J.; Oltra M.A.; Ferrández M. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The pomegranate (Punica granatum L.) is one of the crops in the south of the province of Alicante, where imperfections in the rind caused by pests and diseases are the cause of important economic losses for the producer. The solution to physiopathological fruit damage is still unsolved, whereas pest and disease control is practically mastered as a result of the research carried out by the plant health industry and application of compounds. These compounds, if used appropriately, allow us to keep a good control of plant health problems at a reasonable cost. The present work attempts to revise briefly the present plant health problems (pests, diseases and alterations) which frequently affect the pomegranate in the south of Alicante. The costs of pest control are described and analysed as well as their percentage of the total crop costs. The active material most often used is reported and an analysis is made of the altered fruit as a percentage of the total fruit harvested.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)